DETERMINANTS OF REVEALED COMPARATIVE ADVANTAGE OF INDONESIAâS PLYWOOD 1985 â 2009 - , Rudianto; , Prof. Jinhwan Oh ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study investigates comparative advantage of Indonesiaâs plywood and determinants of its comparative advantage during 1985 â 2009. Using Balassa index, the Revealed Comparative Advantage of Indonesiaâs plywood had increased from 1985 to 1989 but decreased since then. Examination of the factors determining plywoodâs comparative advantage found that three factors are most influential